Unleashing the Potential of Fruit Byproducts in Value-Added Foods for Sustainable Nutrition: A Review (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The global demand for food continues to increase annually due to the persistent growth of the human population. This rising demand ignites a range of challenges, including resource shortage and the substantial waste generated by the agricultural sector. One significant issue is the incomplete consumption of fruits, where various edible components, such as peels, seeds, and cores, are often discarded, leading to considerable food waste on a global scale. Additionally, agricultural byproducts, including seed coats, husks, pomace, and other plant residues, frequently become underutilized, contributing to environmental degradation. To address these concerns, the efficient valorization of food byproducts, particularly fruit residues, represents a promising strategy for enhancing food system sustainability. Many agricultural byproducts, especially those derived from fruits, are rich in bioactive compounds, including dietary fibers, antioxidants, and micronutrients, which could serve as valuable functional ingredients in the food industry. This review provides an overview of recent advancements in the development of functional foods utilizing various agricultural byproducts, with a particular focus on fruit residues. Furthermore, the review highlights the potential nutritional and functional benefits of incorporating these byproducts into food products, offering a pathway to both reduce waste and improve the nutritional profile of food products.
Keywords: Agri food waste; Prebiotic; Probiotic; Lactic acid bacteria; Functional food